2023
DOI: 10.3390/cimb45100507
|View full text |Cite
|
Sign up to set email alerts
|

Tryptase-Positive Mast Cells Promote Adipose Fibrosis in Secondary Lymphedema through PDGF

Takashi Nuri,
Denan Jin,
Shinji Takai
et al.

Abstract: Lymphedema is a chronic and progressive condition that causes physical disfigurement and psychological trauma due to the accumulation of lymphatic fluid in the interstitial space. Once it develops, lymphedema is difficult to treat because it leads to the fibrosis of adipose tissue. However, the mechanism behind this remains unclear. The purpose of this study was to investigate the involvement of mast cells (MCs) in the adipose tissues of patients with lymphedema. We found that fibrosis spread through blood ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Pathohistological studies have identified hyperplasia of collagen fibers and smooth muscle cells, causing thickening of the lymphatic vessels. This contributes to the hardening of the lymphatics, compromising their peristaltic ability and [26][27][28] , lastly, exacerbating the accumulation of lymph. In summary, the pathophysiology of lymphedema results from an inappropriate circle of stasis, causing an imbalance in the interstitial fluids, lymphatic vessel remodeling and function, and adipose tissue deposition.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Pathohistological studies have identified hyperplasia of collagen fibers and smooth muscle cells, causing thickening of the lymphatic vessels. This contributes to the hardening of the lymphatics, compromising their peristaltic ability and [26][27][28] , lastly, exacerbating the accumulation of lymph. In summary, the pathophysiology of lymphedema results from an inappropriate circle of stasis, causing an imbalance in the interstitial fluids, lymphatic vessel remodeling and function, and adipose tissue deposition.…”
Section: Pathophysiologymentioning
confidence: 99%